UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA 2 MELALUI METODE INQUIRY PADA MATERI KASUS-KASUS PELANGGARAN HAK ASASI MANUSIA DALAM PERSPEKTIF PANCASILA DI MAN 2 PIDIE JAYA - Cut Ailiana (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
This research aimed at finding out the increase of learning results of XI Science 2 students by inquiry method on materials of human right violation cases in the Pancasila perspective at MAN 2 Pidie Jaya in academic year 2021/2022. This research belonged to classroom action research (CAR) of which the subject were eighteen students with heterogeneous ability. It was conducted in three phases; pre-cycle, cycle 1 and cycle 2. The data collection was by observation, interview, field notes, and evaluation. The finding showed that there was an increase of students' learning results after applying the method. On pre-cycle, the observation mentioned the mean score was 61,94 in which 16.67% students accomplished the Minimum Completeness Criteria (MCC) . On cycle 1, as many 72.22% of the students reached the MCC with a mean score of 74.44. Last, on cycle 2, 94.44% of the students got 80.83 mean scores of MCC. Therefore, it could be concluded that the application of the inquiry method on the material of human rights violation cases in the perspective of Pancasila could increase the learning result.